2012
DOI: 10.1038/nchembio.775
|View full text |Cite
|
Sign up to set email alerts
|

BCR-ABL uncouples canonical JAK2-STAT5 signaling in chronic myeloid leukemia

Abstract: Constitutive activation of STAT5 is critical for the maintenance of chronic myeloid leukemia (CML) characterized by the BCR-ABL oncoprotein. Tyrosine kinase inhibitors (TKIs) for the STAT5-activating kinase JAK2 have been discussed as a treatment option for CML patients. Using murine leukemia models combined with inducible ablation of JAK2, we show JAK2 dependence for initial lymphoid transformation, which is lost once leukemia is established. In contrast, initial myeloid transformation and leukemia maintenanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
161
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(175 citation statements)
references
References 49 publications
11
161
2
1
Order By: Relevance
“…AG490 generally tends to induce dose-dependent reduction of proliferation and induction of apoptosis, in concentrations where STAT activation was not prevented. 55 Moreover, recent studies have also highlighted the low potency of AG490 for inhibition of Jak2 56 or even the total lack of Jak2-inhibition 57 at concentrations of 5 mM. Our data indicate that Jaks are no suitable drug targets in F/PDGFRa-positive cells and that it is questionable whether patients would benefit from treatment with Jak inhibitors.…”
Section: Discussioncontrasting
confidence: 37%
“…AG490 generally tends to induce dose-dependent reduction of proliferation and induction of apoptosis, in concentrations where STAT activation was not prevented. 55 Moreover, recent studies have also highlighted the low potency of AG490 for inhibition of Jak2 56 or even the total lack of Jak2-inhibition 57 at concentrations of 5 mM. Our data indicate that Jaks are no suitable drug targets in F/PDGFRa-positive cells and that it is questionable whether patients would benefit from treatment with Jak inhibitors.…”
Section: Discussioncontrasting
confidence: 37%
“…Constitutive activation of STAT5 has been demonstrated as a mechanism for the maintenance of chronic myeloid leukemia (CML) characterized by the BCR-ABL fusion (21). We found that DNA binding activity of STAT5 is suppressed when BCR-ABL is inactivated by imatinib.…”
Section: Analysis Of Dynamic Changes Of Global Tf-dna Binding Patternmentioning
confidence: 64%
“…18 Several groups have recently demonstrated the successful targeting of both BCR-ABL-1 and JAK2 in the CML stem cells in in vitro models of CML stem cells procured from imatinib-resistant patients. 19 The notion of combining ABL-1 TKIs and JAK inhibitors, however, remains uncertain at this time. 20 Other candidate pharmacological interventions of interest include innovative methods in targeting the bone marrow microenvironment which can function as a protective factor against TKI-induced apoptosis of CML stem cells and several diverse strategies, including the combination of TKIs with other candidate inhibitors which target diverse signaling pathways, including WNT/β-catenin, Hedgehog, TGF-β/FoxO3a/BCL6 and JAK2/PP2A.…”
Section: Stem Cells and Efforts To Target Themmentioning
confidence: 99%